Recovery of metals from copper converter slag by leaching with K2Cr2O7-H2SO4 - Boyrazlı, Mustafa; Altundoğan, Hamdi Soner; Tümen, Fikret (My University, 2006)
In this study, the effects of some parameters on the extraction of metals from copper converter slag by using a sulphuric acid/potassium dichromate lixiviant were investigated. The leaching kinetic of copper from converter slag was also investigated. The results indicated that increasing the time and temperature have positive effects on the extraction of metals. The best results were obtained by the leaching of converter slag (-200 mesh, 10 g/L of slag/solution ratio) with a lixiviant containing 0.25 M H2SO4 and 0.1 M K2Cr2O7 for 120 minutes at 70 °C. Under these conditions, 99.66% Cu extraction yield was achieved. The kinetic evaluations showed that the extraction of Cu from the converter slag is well represented by the shrinking core model controlled by diffusion through the slag matrix. The activation energy of the leach process was calculated as 33.66 kJ/mol for the temperature range of 25 to 70 °C (298 to 343 K). Also, reaction order with respect to dichromate was determined as first order in the concentration range of 0.025 to 0.1 M at 25 °C (298 K). Dans cette étude, on a étudié l’effet de certains paramètres sur l’extraction de métaux à partir des scories de convertisseur de cuivre en utilisant une solution de lixiviation d’acide sulfurique et de bichromate de potassium. On a également étudié la cinétique de lixiviation du cuivre à partir des scories de convertisseur. Les résultats ont indiqué que l’augmentation de la durée et de la température avait des effets positifs sur l’extraction des métaux. On a obtenu les meilleurs résultats par la lixiviation des scories de convertisseur (maille de –200, rapport de 10 g/L de scories/solution) avec une solution de lixiviation contenant 0.25 M H2SO4 et 0.1 M K2Cr2O7 pendant 120 minutes à 70 °C. Sous ces conditions, on a obtenu un rendement d’extraction de 99.66% de Cu. L’évaluation de la cinétique a montré que l’extraction de cuivre à partir des scories de convertisseur était bien représentée par le modèle du noyau rétrécissant contrôlé par diffusion à travers la matrice de scories. On a calculé l’énergie d’activation du procédé de lessivage à 33.66 kJ/mol dans la gamme de température de 25 à 70 °C (298 à 343 K). Également, on a déterminé l’ordre de réaction par rapport au bichromate comme étant de premier ordre dans la gamme de concentration de 0.025 à 0.1M à 25 °C (298 K).
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Metal recovery; Leaching; Sulphuric acid; Dichromate